2019
DOI: 10.1038/s41598-018-37802-1
|View full text |Cite
|
Sign up to set email alerts
|

The transdiagnostic structure of mental effort avoidance

Abstract: The law of least mental effort states that, everything else being equal, the brain tries to minimize mental effort expenditure during task performance by avoiding decisions that require greater cognitive demands. Prior studies have shown associations between disruptions in effort expenditure and specific psychiatric illnesses (e.g., schizophrenia and depression) or clinically-related symptoms and traits (e.g., anhedonia and apathy), yet no research has explored this issue transdiagnostically. Specifically, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 64 publications
(86 reference statements)
2
45
0
Order By: Relevance
“…Echoing previous work (Kool et al, 2010; Patzelt et al, 2019), results showed that, overall, participants preferred the low-demand option on both sessions, but more interestingly, acute stress increased participants’ preferences for effort avoidance (see Fig. 3), as evidenced by a larger percentage of low-demand choices in the stress condition ( M = 61.53%, SD = 16.47) than in the control condition ( M = 56.16%, SD = 16.30).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Echoing previous work (Kool et al, 2010; Patzelt et al, 2019), results showed that, overall, participants preferred the low-demand option on both sessions, but more interestingly, acute stress increased participants’ preferences for effort avoidance (see Fig. 3), as evidenced by a larger percentage of low-demand choices in the stress condition ( M = 61.53%, SD = 16.47) than in the control condition ( M = 56.16%, SD = 16.30).…”
Section: Resultsmentioning
confidence: 89%
“…Participants are neither rewarded for good performance nor receive any potentially rewarding performance-related feedback during the task. Thus, preferences for the low-demand cue should primarily result from aversion to cognitive effort (Patzelt et al, 2019). Here, the mapping of visual cue to demand level remained constant within participants but was counterbalanced across participants.…”
Section: Demand-selection Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…The study and experimental protocols followed ethical guidelines and were approved by the Committee on the Use of Human Subjects (CUHS), the Institutional Review Board (IRB) for Harvard University. A subset of 377 young adults (<= age 30) and 47 older adults (>= age 56) were selected from a larger study conducted on AMT that examined relationships between psychopathology and model-based control (Patzelt et al, 2019a); and separately, psychopathology and mental effort (Patzelt, Kool, Millner, & Gershman, 2019b). All participants were required to have U.S. residency, 90% approval rating, and 100 completed Mechanical Turk Human Intelligence Tasks.…”
Section: Participantsmentioning
confidence: 99%
“…In the study of human behavior, these principles have inspired the principle of least effort, which was used to explain the power-law form of the rank-frequency distribution of words in the English language 6 , and subsequently a diverse range of phenomena such as crowd behavior 7 and even mental effort 8 . These studies have found predictable patterns in distributions arising from human behaviors, which individually are variable and unpredictable.…”
Section: Introductionmentioning
confidence: 99%